A critical analysis of the implementation of the 'pay now, argue later' principle by SARS as provided by section 164 of the Tax Administration Act 28 of 2011; and, Limitation of interest deduction in South Africa: a suggested approach to the application of sections 31 and 23M of the Income Tax Act 58 of 1962 to debt and equity business financing methods - Tseisi, Hulisani (Department of Commercial Law, 2018)
A critical analysis of the implementation of the 'pay now, argue later' principle by SARS as provided by section 164 of the Tax Administration Act 28 of 2011: Abstract: The 'Pay Now, Argue Later' principle applies in income tax or value-added tax collection procedure after the South African Revenue Services has concluded an assessment in terms of the Tax Administration Act 28 of 2011 and found that an amount of tax is due and payable by the taxpayer. In terms of the 'pay now, argue later' principle, the taxpayer has to pay the assessed amount before being accorded an opportunity to raise any objections. The purpose of this paper is, to do an in-depth evaluation of the implications of the implementation of the 'pay now, argue later' principle by SARS. The implementation of the principle will be evaluated to determine if it is unjust, inequitable or unreasonable. In addition to the latter evaluation, the principle's shortfalls will be highlighted with the inclusion of a brief legal position in other countries. The paper acknowledges the existence of the principle, although the implementation thereof by SARS remains questionable and a source of controversy. The paper ultimately concludes that the 'pay now, argue later' principle, though constitutionally validated to a certain extent need to be revised. A balance has to be struck between the taxpayer's rights, public interest and SARS' powers in implementing the principle. A recommendation is therefore made to place the implementation thereof in the Tax Ombud in view of UK's Taxes Management Act where Commissioners resolve such disputes between taxpayers and the Inland Revenue Authority. ******************************************* Limitation of interest deduction in South Africa: a suggested approach to the application of sections 31 and 23M of the Income Tax Act 58 of 1962 to debt and equity business financing methods. Abstract: The South African income tax system acknowledges the financing of resident companies by a related non-resident company through the use of debt and equity. However, the use of debt financing method is a cause for concern to the South African Revenue Services as it results in the base erosion and profit shifting of taxable profits through mispricing and excessive interest deductions. Section 31 and 23M were inserted into the South African Income Tax Act 58 of 1962 to address excessive debt levels and interest deductions. The objective of this paper is to analyse the rationale behind the use of debt and equity financing methods. This paper will also discuss the application of both s 31 and s 23M. Due to the close connection of s 31 and s 23M to debt transactions, an approach on how the two sections can be applied is suggested. This paper finds that the provisions of both s 31 and s 23M are applicable to the same set of facts. The paper also finds that s 31 provisions are applied to determine if a company has excessive debts taking into account the arm's length principle while s 23M provisions are applied to limit interest deductions. The paper suggests that the legislature should provide guidance on the interplay of the two provisions and in the absence of any guidance, the provisions of s 31 should be applied first followed by the provisions of s 23M.